Exorcising the Past: History, Hauntings and Evil in Neo-Gothic Fiction - Van der Wielen, Karlien (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2016)
This thesis explores the conventions of both historical and Gothic fiction in order to investigate what seems to be a recurrent impulse to exorcise the past in what I define as contemporary Neo-Gothic fiction. It therefore attempts to establish a distinction between Neo-Gothic fiction and other forms of contemporary Gothic fiction by focusing on the treatment of history, the supernatural and the grand narrative of progress in three contemporary Gothic novels: The Little Stranger by Sarah Waters, The Historian by Elizabeth Kostova and The Accursed by Joyce Carol Oates. This thesis argues that the most potent manifestation of history can be found in the representation of the revenant in Neo-Gothic fiction, which exhibits a disruptive and evil ontology that problematises the exorcism of the past. Furthermore, the reactions of 'modern' characters to these revenants illustrate the imperative to exorcise the past, and therefore the treatment of history and the past is reflected in the interaction between the 'modern' characters and the Gothic revenants. Through this interaction as well as the parody of traditional Gothic and historical fiction conventions, Neo-Gothic fiction constructs a critique of the Enlightenment's grand narrative of progress. Paradoxically, this constitutes Neo-Gothic fiction's own attempt to exorcise the past, which it recognises in a simplified and reductive narrative of history propounded through the grand narrative of progress. This thesis therefore pays particular attention to the configuration of revenants as evil and 'modern' humans as good, and the disruption of this simple binary that is effected through Neo-Gothic fiction's subversion of the grand narrative of progress. This focus allows for the theorisation of the revenant through Jacques Derrida's notion of 'hauntology' and Julia Kristeva's 'the abject', the investigation of the treatment of history in Neo-Gothic fiction and the exploration of very recent Gothic texts that have not yet received much critical attention.
Keywords: Uncatalogued